Shaping the Soundscape: Exploring the Influence of Building Layout on Outdoor Acoustic Environments - Hamouta, Sami; Ahriz, Atef; Zemmouri, Noureddine; Mansouri, Ahmed (Archives of Acoustics, 2026)
This study investigated the influence of building layout on the outdoor acoustic environment through field measurements conducted in four courtyards at the University of Batna 1. Acoustic parameters including sound pressure level (SPL) attenuation, reverberation time (RT), early decay time (EDT), clarity (D50), and the rapid speech transmission index (RaSTI) were evaluated. Results showed that square-shaped courtyards retained sound the longest (RT20 exceeding 2.3 s at 1000 Hz), U-shaped courtyards exhibited the most irregular reverberation patterns, and linear courtyards provided the most stable sound decay. The D50 and RaSTI values were highest in linear courtyards, indicating superior speech intelligibility, while square and U-shaped layouts demonstrated reduced intelligibility due to extended reverberation. The SPL attenuation was also more consistent in linear configurations compared to the variable patterns observed in enclosed geometries. These findings demonstrate that building form plays a decisive role in shaping outdoor acoustic conditions and highlight the importance of considering acoustic performance in early design decisions. The results are broadly applicable to the planning of courtyards, plazas, and semi-enclosed urban spaces. Future work should explore additional variables such as building height, fa¸cade materials, vegetation, and seasonal effects to develop comprehensive guidelines for acoustically optimized outdoor environments.